The Human Dimension of Nuclear Security: Legacy of the Nuclear Security Summit - Franca Padoani (International Journal of Nuclear Security, 2020)
A deeply rooted nuclear security culture and adequate human resources at all levels – involving regulators, the law enforcement agencies, academia, industry - are universally recognized as the foundation of a robust and sustainable nuclear security regime, national and global. International cooperation and networks are fundamental elements in ensuring the development and sustainability of what may be called the “human dimension” of Nuclear Security, and the Nuclear Security Summit (NSS) process has been the cornerstone for their consolidation.
Keywords: nuclear security; nuclear security culture; capacity building